Efficiency Enhancement of ZnO Dye-sensitized Solar Cells by Modifying Photoelectrode and Counterelectrode - Kritsada Hongsith (2018)
© 2015 The Authors. Published by Elsevier Ltd. In this research, ZnO photoelectrode and Platinum counterelectrode in dye-sensitized solar cells (DSSCs) were modified by sparking technique and investigated photoconversion properties. The ZnO photoelectrode was adjusted by using double-layered technique. Here, the DSSC structures were FTO/double-layered ZnO/N719/electrolyte/Pt counterelectrode. The efficiency characteristics for DSSCs were measured under illumination of simulated sunlight with the radiant power of 100 mW/cm 2 . It was found that the best results of DSSCs were observed with power conversion efficiency of 2.53% at 250 sparking cycles for ZnO nanopowder over-layered which was significantly higher than 1.83% of the reference cell. The efficiency enhancement can be explained by the arising of short-circuit photocurrent due to increasing of light scattering and dye adsorption for double-layered photoelectrode and the increasing of the active surface area of Platinum nanoparticles in counterelectrode.